1993
DOI: 10.1073/pnas.90.5.1686
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed phytoplankton supply to the rocky subtidal zone: influence of internal waves.

Abstract: Hydrographic measurements indicate that the thermocline and the phytoplankton-rich chlorophyll maximum layer are vertically displaced over a rocky pinnacle in the central Gulf of Maine by internal waves with maximum amplitudes of 27 m. Such predictable downwelling events are linked to rapid, 2-to 3-fold increases in chlorophyll a, an indicator of phytoplankton concentration, in pulses of warm water recorded 4 cm above the bottom (29-m depth). The 1.5-5.6'C temperature fluctuations had an average period of 10.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 18 publications
0
40
0
Order By: Relevance
“…Our study suggests that bottom-up processes may be important to sponge bioenergetics and energy transfer on Conch Reef, but more work is needed to identify the biological and/or physical processes responsible for increased food availability at deeper depths. Other studies have indicated that internal wave activity on Conch Reef (Leichter et al 1996(Leichter et al , 1998(Leichter et al , 2003 and elsewhere (Witman et al 1993(Witman et al , 2004) may enhance food availability at deeper depths during the stratified season. However, because our measurements were performed during non-internal wave conditions, this phenomenon probably plays an ancillary role in producing depth-specific differences in food availability.…”
Section: Discussionmentioning
confidence: 97%
“…Our study suggests that bottom-up processes may be important to sponge bioenergetics and energy transfer on Conch Reef, but more work is needed to identify the biological and/or physical processes responsible for increased food availability at deeper depths. Other studies have indicated that internal wave activity on Conch Reef (Leichter et al 1996(Leichter et al , 1998(Leichter et al , 2003 and elsewhere (Witman et al 1993(Witman et al , 2004) may enhance food availability at deeper depths during the stratified season. However, because our measurements were performed during non-internal wave conditions, this phenomenon probably plays an ancillary role in producing depth-specific differences in food availability.…”
Section: Discussionmentioning
confidence: 97%
“…These phenomena are widespread in both coastal and offshore oceans (Wolanski 1994, Pineda 1995 and represent an important mechanism of high frequency mixing and transport across density discontinuities (Sandstrom & Elliot 1984, Wolanski 1994, Shanks 1995. In the rocky subtidal of the Gulf of Maine, unbroken internal waves can produce downward, vertical deflection of the thermocline that brings a subsurface chlorophyll maximum layer into contact with dense aggregations of benthic suspension feeders (Witman et al 1993). While floating, neustonic material may be transported in surface slicks produced by trains of subsurface internal waves (Shanks 1983, 1986, Kngsford & Choat 1986; horizontal transport at the pycnocline by internal waves in deep water should be slow at best.…”
Section: Weight Volumementioning
confidence: 99%
“…Frederiksen et al (1992) suggested suspended particle delivery by internal waves could explain patchy distributions of a deep-water scleractinian coral in the northeastern Atlantic. Witman et al (1993) documented transport of warm, phytoplankton-rich water to dense aggregations of sessile suspension feeders on shallow pinnacles in the Gulf of Maine. Andrews and Gentien (1982), Wolanski and Pickard (1983), and Wolanski (1994) have pointed to tidal oscillations of the thermocline in the Coral Sea as a potential source of nutrients for the outer shelf of the Great Barrier Reef, and Novozhilov et al (1992) reported evidence of tidal upwelling near reefs in the Seychelles Islands.…”
mentioning
confidence: 99%